Impact of COVID-19 pandemic on outpatient visit volume in cancer patients: Results of COMETA multicenter retrospective observational study - Frisardi, Vincenza; Brunetti, Oronzo; Abbinante, Vincenza; Ardigò, Marco; Caolo, Giuseppina; Di Turi, Annunziata; Torsello, Alessandra; Napoli, Christian; Mancini, Rita; Belleudi, Valeria; Addis, Antonio; Di Bella, Ornella; et al. (Frontiers in Public Health, 2023)
Objective To evaluate the impact of the COVID-19 pandemic on first and follow-up visits for cancer outpatients. Methods This is a multicenter retrospective observational study involving three Comprehensive Cancer Care Centers (CCCCs): IFO, including IRE and ISG in Rome, AUSL-IRCCS of Reggio Emilia, and IRCCS Giovanni Paolo II in Bari) and one oncology department in a Community Hospital (Saint'Andrea Hospital, Rome). From 1 January 2020 and 31 December 2021, we evaluated the volume of outpatient consultations (first visits and follow-up), comparing them with the pre-pandemic year (2019). Results were analyzed by quarter according to the Rt (real-time indicator used to assess the evolution of the pandemic). IFO and IRCCS Giovanni Paolo II were “COVID-free” while AUSL-IRCCS RE was a “COVID-mixed” Institute. Depending on the Rt, Sain't Andrea Hospital experienced a “swinging” organizational pathway (COVID-free/ COVID-mixed). Results Regarding the “first appointments”, in 2020 the healthcare facilities operating in the North and Center of Italy showed a downward trend. In 2021, only AUSL-IRCCS RE showed an upward trend. Regarding the “follow-up”, only AUSL IRCCS RE showed a slight up-trend in 2020. In 2021, IFO showed an increasing trend, while S. Andrea Hospital showed a negative plateau. Surprisingly, IRCCS Giovanni Paolo II in Bari showed an uptrend for both first appointment and follow-ups during pandemic and late pandemic except for the fourth quarter of 2021. Conclusions During the first pandemic wave, no significant difference was observed amongst COVID-free and COVID-mixed Institutes and between CCCCs and a Community Hospital. In 2021 (“late pandemic year”), it has been more convenient to organize COVID-mixed pathway in the CCCCs rather than to keep the Institutions COVID-free. A swinging modality in the Community Hospital did not offer positive results in term of visit volumes. Our study about the impact of COVID-19 pandemic on visit volume in cancer outpatients may help health systems to optimize the post-pandemic use of resources and improve healthcare policies.